Pura Veteran: Hubungan Makna Simbol Agama dan Negara di Pura Pejuang Taman Suci di Desa Tua, Kabupaten Tabanan, Bali - I Wayan Wastawa; I Ketut Sudarsana (Pusat Kajian Bali Universitas Udayana, 2019)
This study discusses the relationship of religious symbols and state symbols in the Taman Suci Temple, also known as Pura Veteran, in the Tua Village, Tabanan, one of the locations for Balinese fighters in defending Indonesian independence from Dutch attacks in 1946. Besides religious symbols, in the Veteran Temple there are also state symbols such as the Garuda Pancasila decoration, the Red and White flag, and advice on fighting sharp bamboo. Data from this qualitative study were obtained from field observations, library studies, and interviews. Data analysis is carried out with critical interpretive methods which include reduction steps, classification, interpretation, and making conclusions. The article concludes that Pura Vetaran has a socio-religious function as a means of social interaction, fosters Hindu social solidarity, and socio-political functions to arouse nationalism as concerned with the use of the Garuda Pancasila symbol and the Red and White of national flag.